RELEVANSI PEMIKIRAN EKONOMI MENURUT UMER CHAPRA DAN KONSEP UANG MENURUT AL-GHAZALI - Ghana Qonitati Hanani; Vinny Kurniaty (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Economic development at this time is not without the role of previous leading scientists. Where concepts and ideas remain used in any economic and state development activity. M. umer chapra is one of the scientists known for the concept of justice in economic development, which is an islamic economy alternative to achieving moral and justice economic development. And al-ghazali the islamic scholar famous for his maqashid philosophy. Where the building of a country cannot escape the role of keeping 5 things: keeping religion (hifdzu din), keeping the soul (hifdzu nafs), keeping sense (hifdzu aql), keeping descendants (hifdzu nasl) and keeping property (hifdzu mal). Both concepts are presented and articulated in a way that both lead to justice, prosperity and morals in economic development.